Analisis Kedudukan Perma No. 1 Tahun 2016 Tentang Prosedur Mediasi Sebagai Dasar Penyelesaian Perselisihan Yang Bermuatan Tindak Pidana Dalam Perspektif Hukum Pidana - Surya, Muhammad Langga; Falahiyati, Nurhimmi; Sahbudi, Sahbudi (Jurnal Ilmiah Penegakan Hukum, 2025)
This study examines the legal status of the Indonesian Supreme Court Regulation (PERMA) No. 1 of 2016 on Mediation Procedures when applied to disputes containing criminal elements. Although PERMA is primarily designed to strengthen mediation mechanisms in civil cases, in practice many disputes originate in the civil domain but subsequently generate criminal consequences, such as fraud allegations arising from loan agreements, domestic violence emerging from family conflicts, or embezzlement issues stemming from business disputes. These situations raise questions regarding the extent to which PERMA may influence or serve as a basis for resolving cases involving criminal offenses. Using a normative juridical method with statutory, conceptual, and case approaches, this study finds that PERMA is hierarchically subordinate to statutory laws and therefore cannot override the Indonesian Criminal Code (KUHP) or the Criminal Procedure Code (KUHAP). Consequently, PERMA cannot serve as a legal basis for terminating criminal proceedings, as such mechanisms are strictly regulated under KUHAP. Nevertheless, the principles of mediation embodied in PERMA can be adopted analogically to support restorative justice, particularly in minor offenses or complaint-based crimes. Peace agreements may be considered by judges in sentencing or by prosecutors in applying the principle of opportunity. Thus, while PERMA cannot halt criminal processes, it can function as a normative reference that strengthens a more humanistic and efficient approach to criminal case resolution without compromising legal certainty.